General principles of communication among nurses in a long-term care unit: a best practice implementation project - Felizardo, Helena; Cardoso, Daniela; Nogueira, Paula; Bastos, Joana; Casimiro, Daniela; Nogueira, Pedro; Cardoso, Ana Filipa; Apóstolo, João; Vrbová, Tereza; Klugar, Miloslav; Klugarová, Jitka (JBI evidence implementation, 2025)
INTRODUCTION: In health care, effective communication enhances teamwork and safety by minimizing adverse events. Evidence suggests that ongoing education should include communication skills training, as interprofessional communication relies on tools that facilitate seamless interaction. OBJECTIVE: This project aimed to improve communication practices among nurses in a long-term care unit by promoting evidence-based recommendations. METHODS: This project followed the seven phases proposed by the JBI Evidence Implementation Framework. This framework is grounded in an audit, feedback, and re-audit process, along with a structured approach to addressing barriers to compliance with best practices. JBI's Practical Application of Clinical Evidence System (PACES) and Getting Research into Practice (GRiP) approach were also used. RESULTS: A baseline audit was conducted focusing on three audit criteria. Compliance was measured by observing 250 handovers and administering a questionnaire to 14 nurses. After analyzing the results, the nursing team identified barriers and designed strategies to promote change, such as educational sessions and a focus group. The results of the follow-up audit showed significant improvements across all criteria. Nurses received training in communication for Criterion 1, which improved from 0% to 78%. For Criterion 2, training in teamwork and conflict management improved from 21% to 50%. For Criterion 3, the use of a structured communication tool (ISBAR) during handovers improved from 43.6% to 91%. CONCLUSIONS: The nursing team's involvement enabled effective change. Adapting ISBAR to a long-term care unit was an unexpected goal. The next objective is to refine and share it with similar units. Integrating communication training into health care institutions' priorities is crucial, and future audits will ensure sustainability. SPANISH ABSTRACT: http://links.lww.com/IJEBH/A295.
Keywords: lékařská praxe založená na důkazech; komunikace; Humans; Long-Term Care; Interprofessional Relations; průzkumy a dotazníky; lidé; Patient Handoff; Evidence-Based Practice; Surveys and Questionnaires; předání pacienta do jiné péče; Communication; dlouhodobá péče; interprofesionální vztahy